My bucket list - Joshi, Keshav Das (Journal of Society of Surgeons of Nepal, 2016)
Son of Ram Das Joshi, Prof Keshav Das Joshi was born at Kathmandu. He completed MBBS on 1968 from Trivandrum Kerela, residency (1970 to 1974) in MS (General Surgery) on 1974 from AIIMS, New Delhi. He served as a registrar on 1975 at Maulana Azad Medical College and training in Clinical Oncology in Tokyo at the National Cancer Hospital) on 1983. He had his training in Plastic Surgery in U.K. 1987 and various periods of training and Observation in Burn & Plastic Surgery in Canada, Belgium, France, Singapore and Switzerland. Since 2032 he has worked as a general surgeon in Butwal Hospital, Lumbini Anchal, Bheri Anchal Hospital followed by six years in Gandaki Zonal Hospital a total of 10 years. The history of Burns and Plastic surgery services in Nepal was started in Bir hospital. The separate Burns and Plastic surgery unit was established in the year 1998 AD. Dr Keshav Das Joshi, senior consultant plastic surgeon, proposed it. In his endeavor the first organized Burn Unit was established in 2000 A.D. For his contribution to the society he has been felicitated by the government by ‘Gorkha Dakshin Bahu’ Third, ‘Trishaktipatta’ Third, ‘Birendra Aishworya Sewa Padak’ etc to name a few. He served as the president of Society of Surgeon of Nepal for the period 1999 – 2002. He served as the editor of souvenir of the third International Surgical Conference of SSN on 1994. He had a major role in the establishment of the Journal of Society of Surgeons of Nepal (JSSN). He served as the chief editor for the period 1998, 1999.